Morphological and anatomical studies of Conamomum vietnamense N.S. Lý & T.S. Hoang: An endemic plant from Vietnam - NGUYEN THANH TO NHI; TRAN VAN CHEN; DUONG NGUYEN XUAN LAM; DANH DUC NGUYEN; QUANG DIEP DINH; NGUYEN HOANG KHANH LINH (Society for Indonesian Biodiversity, 2023)
Abstract. Nhi NTT, Chen TV, Lam DNX, Nguyen DD, Dinh QD, Linh NHK. 2023. Morphological and anatomical studies of Conamomum vietnamense N.S. Lý & T.S. Hoang: An endemic plant from Vietnam. Biodiversitas 24: 5022-5034. Conamomum vietnamense N.S. Lý & T.S. Hoang (Zingiberaceae) is an endemic plant from Vietnam. Information on the anatomical structure of leaves, roots, rhizomes, and the powder characteristics of C. vietnamense has not been reported. This study aimed to combine macro- and micro-morphological analysis to identify C. vietnamense accurately. Twenty fresh plants were randomly collected from the wild habitats in Vietnam were used for the study. Macromorphological characteristics were observed and compared to earlier research. Iodine green-carmine staining was then used to histologically examine the leaves, roots, and rhizomes. The powdered rhizome and leaf features were described via a microscope. Macromorphologically, C. vietnamense is characterized by its stout stilt roots, short petioles, oblong-lanceolate leaf blades with lightly plicate, inflorescences with obovoid, and narrowly ovate bracts, hairy underside bracteoles, bilobed calyx, yellow flowers with broadly obovate, glabrous, trilobed labellum. Micromorphologically, the anatomical features of leaves, roots, and rhizomes have similarities with those of Zingiberaceae species. The tetracytic stomata was observed on both leaf surfaces. The stomatal indexes on the abaxial and adaxial surfaces of the leaves are 8.81±0.55% and 0.1±0.06%, respectively. Calcium oxalate crystals were found in the leaf. Starch grains and reticulate xylem vessels were present only in rhizome powder. These findings are important characteristics for identifying C. vietnamense.